Evolution of the 'Modern' Transitory Shelter and Unrecognized Settlements of the Negev Bedouin. (1st December 2011) - Meir, Isaac; Stavi, Ilan
This study reviews the factors involved in the transition from the traditional Bedouin 1 black tent to the tin shack. 2 Many economic, social, and macro-political factors are involved in this transition. It is shown that in functional terms the tin shack is very similar to the traditional tent. However, compared with the traditional tent, the climatic performance of the tin shack is much worse, amplifying ambient temperature extremes, and increasing respiratory related complications. In spite of this poor performance, tin shacks have become the mainstream dwelling form of Bedouin settlements in the Negev during the last three decades.